Neonatal and fetal therapy of congenital diaphragmatic hernia-related pulmonary hypertension. Issue 5 (24th December 2021) - De Bie, Felix R; Avitabile, Catherine M; Joyeux, Luc; Hedrick, Holly L; Russo, Francesca M; Basurto, David; Deprest, Jan; Rintoul, Natalie E
Abstract : Congenital diaphragmatic hernia (CDH) is a complex malformation characterised by a triad of pulmonary hypoplasia, pulmonary hypertension (PH) and cardiac ventricular dysfunction. Much of the mortality and morbidity in CDH is largely accounted for by PH, especially when persistent beyond the neonatal period and refractory to available treatment. Gentle ventilation, haemodynamic optimisation and pulmonary vasodilation constitute the foundations of neonatal treatment of CDH-related PH (CDH-PH). Moreover, early prenatal diagnosis, the ability to assess severity and the developmental nature of the condition generate the perfect rationale for fetal therapy. Shortcomings of currently available clinical therapies in combination with increased understanding of CDH pathophysiology have spurred experimental drug trials, exploring new therapeutic mechanisms to tackle CDH-PH. We herein discuss clinically available neonatal and fetal therapies specifically targeting CDH-PH and review the most promising experimental treatments and future research avenues. Abstract : This review looks at the current clinically available neonatal and fetal therapies targeting congenital diaphragmatic hernia and the associated pulmonary hypertension, and considers the most promising experimental treatments and future research.